Rapid Detection to Differentiate Hypervirulent Klebsiella pneumoniae (hvKp) From Classical K. pneumoniae by Identifying peg-344 With Loop-Mediated Isothermal Amplication (LAMP) - Liao, Wenjian; Long, Dan; Huang, Qisen; Wei, Dandan; Liu, Xiaobing; Wan, Lagen; Feng, Yuling; Zhang, Wei; Liu, Yang (Frontiers in Microbiology, 2020)
Objectives: To establish a rapid molecular diagnostics of hvKp using the peg-344 loop-mediated isothermal amplification technique (LAMP). Methods: In all, 28 K. pneumoniae strains isolated from the blood of patients were used for the peg-344 LAMP. K. pneumoniae NTUH-K2044 and K. pneumoniae ATCC700603 were used as positive control and negative control, respectively. For comparison, all the results were detected in a polymerase chain reaction (PCR), which was considered the gold standard for the detection of the gene. Mouse lethality assay, and Serum killing assay were also used to determine the virulence phenotype of K. pneumoniae. Results: We determined the specificity and sensitivity of the primers for peg-344 detection in the LAMP reactions. This LAMP assay was able to specifically differentiate hvKp from classical K. pneumoniae(cKp) at 65°C, which was 100-fold more sensitive than a PCR assay for peg-344 detection. The virulence phenotype of K. pneumoniae detected by LAMP was as precise as by Mouse lethality assay and Serum killing assay. Conclusion: The LAMP assay is easy to perform and rapid. Therefore, it can be routinely applied to differentiate hvKp from cKp in the clinical laboratory.